EFFECTIVE USE OF ANALYTICAL METHODS IN SOLVING PRACTICAL PROBLEMS OF CERTAIN DYNAMIC PROCESSES - Ma’murov, Talatjon Tursunpoʻlotovich; Arziqulov, Husan Normurodovich (SCIENCE and SOCIETY, 2026)
The article examines the effective use of analytical methods in case analysis of systems whose mathematical models are represented by second-order nonlinear differential equations. Mathematical models of complex processes encountered in many fields, such as physics, mechanics, electrical engineering, and biology, are represented by nonlinear differential equations, and it is important to obtain solutions analytically.
Keywords: differential equation; analytical solution; small parameter method; Adomian series expansion method; homotopy analysis method; Van der Pol equation; mathematical modeling; oscillatory processes